atjournals.com A Study to Evaluate the Knowledge on Prevention of Pressure Ulcer Among B. Sc. (N) Student Nurses in Selected Nursing Colleges, At Palakkad - D. Titus Fernandaz (Research & Review: Management of Emergency and Trauma Nursing (e-ISSN: 2582-0494), 2021)
Pressure ulcer also been called Bed Sores, Pressure Ulcer Sores, Decubitus Ulcer and dermal client have a greater risk of developing pressure ulcers. In reality many cases, pressures, shears, friction and moisture and all may have contributed towards varying degrees to the development of the ulcers. The present study is conducted “To evaluate the knowledge on Prevention of Pressure Ulcer among B.Sc (N) student nurses in selected nursing colleges, at Palakkad”. Quantitative approach with descriptive research design was used for the present study. data was collected at Nehru College of Nursing at Palakkad. The population was who fulfilled inclusion criteria. The sample size for the present study was 60. Non probability convenient sampling technique was used in this study. Structured questionnaire (pieper’s pressure ulcer knowledge test) to assess the knowledge on prevention of pressure ulcer. The collected data was analyzed through descriptive and inferential statistics. The study revealed that maximum student nurses had moderate level of knowledge on prevention on pressure ulcer.